Electrode grid line preparation method and photovoltaic cell
The method addresses screen printing limitations by using a polymer-based process to create precise electrode grid lines, reducing waste and costs, and improving photovoltaic cell efficiency and stability.
Patent Information
- Application Number
- CN202411372836.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2024-12-27
AI Technical Summary
Existing screen printing technologies for photovoltaic cells face challenges in printing accuracy, waste generation, environmental safety, and production efficiency, leading to performance degradation and high costs.
A method involving forming a polymer layer on a substrate, pressing a mold to create grooves, applying conductive material, and sintering to form electrode grid lines, utilizing water-soluble polymers and controlled etching to ensure precise patterning and minimal waste.
Achieves high precision, low cost, and efficient production of electrode grid lines with improved conductivity and stability, reducing waste and environmental impact while enhancing photovoltaic cell performance.
Smart Images

Figure CN119208455A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of photovoltaic technology, and in particular to a method for preparing an electrode grid line and a photovoltaic cell. Background Art
[0002] In the world today, burning coal is still the main way to generate electricity. However, with the acceleration of industrialization and the continuous increase in energy consumption, the reserves of non-renewable resources such as coal are gradually decreasing, and their mining and use have caused increasingly serious negative impacts on the environment. Therefore, in order to reduce dependence on fossil fuels and promote sustainable development, countries have sought alternatives to renewable energy, among which solar energy has received widespread attention as a promising clean energy source. Photovoltaic silver paste, as a key material for solar cells, has an important influence on cell performance. By optimizing the coating process of photovoltaic silver paste on solar crystalline silicon wafers, the conductivity and photoelectric conversion efficiency of solar cells can be significantly improved.
[0003] At present, screen printing technology is mainly used in industrial production to plate electrodes on photovoltaic cells. Although screen printing technology is widely used because it is suitable for large-scale production, it still faces a series of technical challenges in practical applications. First, insufficient printing accuracy is a major problem. Due to changes in printing parameters and instability in the process, the width and thickness of the silver paste are often uneven. This unevenness will lead to an increase in the resistance of the cell, which in turn affects the performance of the cell. In addition, screen printing technology has difficulty in achieving high-resolution pattern printing below 10 microns, which limits its effectiveness in more sophisticated applications.
[0004] Secondly, the waste problem generated during the screen printing process is also an important challenge. The waste of silver paste not only increases production costs, but also brings environmental burdens. Safety issues cannot be ignored either. The solvents and materials used in screen printing may release harmful or irritating dust and gases, which pose a potential threat to the health of operators and the environment. Finally, screen printing has low production efficiency, high requirements for the cleanliness of the production environment, and its relatively slow process speed cannot meet the needs of large-scale production.
[0005] Therefore, it is necessary to develop an electrode grid line printing technology with high printing accuracy, low production cost, high production efficiency, and safety and reliability to promote the sustainable development of photovoltaic cell production. Summary of the invention
[0006] In order to develop an electrode grid line printing technology with high printing accuracy, low production cost and high production efficiency, the present application provides an electrode grid line preparation method and a photovoltaic cell.
[0007] The present application provides an electrode grid line preparation method and a photovoltaic cell using the following technical solutions: A method for preparing electrode grid lines, comprising the following steps: S1, providing a substrate, and forming a polymer layer on the substrate; S2, providing a mold corresponding to the required electrode pattern, and using the mold to press out grooves corresponding to the electrode pattern on the polymer layer; S3, applying a conductive material on the polymer layer so that the conductive material fills the grooves, and scraping off excess conductive material; S4, drying the conductive material; S5, after drying, dissolving the polymer layer; S6, sintering the conductive material to form the electrode grid lines.
[0008] By adopting the above technical solution, the process of scraping and coating the conductive material can be accurately controlled through the design of the mold and the groove, so that the thickness of the conductive material can be effectively controlled to avoid performance degradation caused by uneven thickness. This method can form a fine electrode pattern of several microns on the substrate, ensuring the high precision and high consistency of the electrode grid lines; and this method almost does not generate waste, greatly reducing the amount and cost of conductive materials, and the saved conductive materials can reduce production costs and improve economic benefits; this method has a simple process and high process precision, can achieve rapid production, improve production efficiency, meet the needs of industrial production, and can be in line with the concept of green and sustainable development, which will help promote the application of environmentally friendly production processes.
[0009] In a specific implementation manner, in S2, the thickness of the imprinted residual layer is 0.5-2 μm.
[0010] By adopting the above technical solution, in the process of pressing the groove through the mold, a distance of 0.5~2μm is left between the groove and the substrate, which can effectively avoid direct contact between the membrane and the substrate, thereby reducing the risk of substrate rupture caused by mechanical stress, helping to maintain the integrity of the substrate during operation and improving the stability and reliability of the entire system.
[0011] In a specific possible implementation manner, step S2-1 is further included between S2 and S3: removing part of the polymer layer so that the bottom wall of the groove is on the same level as the top surface of the substrate.
[0012] By adopting the above technical solution, by weakening the height of the polymer layer, the bottom of the groove is made to be in the same plane as the substrate, so that the conductive material subsequently applied in the groove can directly contact the substrate, thereby enhancing the conductive performance and contact quality of the conductive material, and ensuring that the conductive material can form a more stable electrode structure, thereby improving production efficiency and yield rate.
[0013] In a specific implementation manner, in S2-1, the polymer layer is etched by reactive ion etching technology to remove a portion of the polymer layer.
[0014] By adopting the above technical solution, reactive ion etching technology can be used to accurately remove part of the polymer layer, ensuring that the bottom wall of the groove and the top surface of the substrate are on the same horizontal plane. Reactive ion etching can remove the polymer layer in a relatively short time, while providing a uniform etching effect and maintaining the surface quality of the bottom of the groove, thereby ensuring that the conductive material can directly contact the substrate and improve the conductive performance.
[0015] In a specific embodiment, in S2, the groove is hot-pressed on the polymer layer by the mold, and the hot-pressing temperature is 100-180°C.
[0016] By adopting the above technical solution, within this temperature range, the polymer layer can be evenly pressed into the mold to form a clear and accurate groove structure, thereby improving the quality and consistency of the product. The relatively low hot pressing temperature can reduce thermal damage to the polymer layer, avoid polymer degradation or failure due to excessive temperature, maintain the performance and stability of the material, and thus improve production efficiency and product consistency.
[0017] In a specific implementation manner, in S4, the drying temperature of the conductive material is 100-200°C.
[0018] By adopting the above technical solution and utilizing this temperature range, it can be ensured that the conductive material is fully dried to form a stable conductive layer, and it helps to enhance the adhesion between the conductive material and the substrate, reduce the risk of peeling or falling off, and improve its electrical properties and conductivity.
[0019] In a specific embodiment, the material of the polymer layer is a water-soluble polymer material.
[0020] By adopting the above technical scheme, water-soluble polymer materials can be processed through simple dissolution and coating processes, which simplifies the production process, and because water is used as a solvent, these materials are more environmentally friendly and reduce the use of organic solvents and waste disposal problems.
[0021] In a specific embodiment, the water-soluble polymer material is one of polyvinyl alcohol, polyvinyl pyrrolidone, polyethylene glycol, modified polyvinyl alcohol, sodium polyacrylate, polyvinyl alcohol-polyacrylic acid, and polyvinyl alcohol-polyacrylonitrile.
[0022] In a specific embodiment, in S5, hot water at 60-80° C. is used to dissolve the polymer layer.
[0023] By adopting the above technical solution, a higher temperature is used to accelerate the dissolution process of the polymer, shorten the processing time, and improve production efficiency. In addition, hot water helps to overcome the crystalline structure of the polymer, making it dissolve more evenly and forming a more stable solution.
[0024] In a specific embodiment, in S6, the sintering temperature of the conductive material is 600-800°C.
[0025] By adopting the above technical solution, high-temperature sintering is used to form a strong connection between the particles of the conductive layer, thereby improving the bonding force between the layers and reducing the peeling problem, thereby enhancing the mechanical strength and stability of the overall structure. Moreover, at high temperatures, the particles in the conductive material can be effectively fused, significantly improving the conductivity and optimizing the conductive performance.
[0026] In a specific implementation manner, the substrate is made of one of single crystal silicon, polycrystalline silicon, gallium arsenide, cadmium telluride, and amorphous silicon film.
[0027] In a specific embodiment, the conductive material is one of silver paste, copper paste, aluminum paste and a mixture thereof.
[0028] By adopting the above technical solutions, silver paste can provide excellent electrical conductivity, help reduce the resistance of electronic devices, improve performance and efficiency, and provide efficient and stable conductive properties, while adapting to different substrates and manufacturing processes to meet the needs of high-performance electronic products.
[0029] In a specific possible implementation manner, the longitudinal cross-section of the groove is a shape of a rectangle or a trapezoid.
[0030] In a specific embodiment, the substrate of the mold is one of a single crystal silicon substrate, a polycrystalline silicon substrate, a glass substrate, a quartz substrate, a polymer substrate, a copper substrate, a nickel substrate, a copper-nickel alloy substrate, a nickel-iron alloy substrate, an iron-aluminum alloy substrate, and an aluminum alloy substrate.
[0031] A photovoltaic cell comprises the electrode grid lines prepared by the preparation method described above.
[0032] By adopting the above technical scheme, the electrode grid lines prepared by the above preparation method bring high precision, high conductivity, good surface finish, optimized thermal management, and enhanced mechanical strength and durability to the photovoltaic cells, which comprehensively improves the performance, efficiency and long-term stability of the photovoltaic cells; precise grooves are pressed into the polymer layer by a mold to ensure the high precision of the electrode grid line pattern, and this precise patterning helps to optimize the photoelectric conversion efficiency and current collection capacity of the photovoltaic cell; the conductive material is filled and dried and sintered twice, so that the electrode grid lines have excellent conductivity, and the highly conductive electrode grid lines can effectively collect the current generated by the battery, reduce resistance and energy loss, and thus improve the overall power output of the battery; the preparation method supports different electrode pattern designs, so that the structure of the electrode grid lines can be optimized according to the specific needs of the photovoltaic cell, and the flexible design can improve the photoelectric conversion efficiency and adapt to different application scenarios.
[0033] In a specific possible implementation manner, the longitudinal cross-section of the electrode grid line is rectangular or trapezoidal, the height of the rectangle is 10±2 μm, the aspect ratio of the rectangle is 2:1, the base angle of the trapezoid is 30°-70°, the height of the trapezoid is 10±2 μm, and the aspect ratio of the trapezoid is 2:1.
[0034] In summary, the beneficial technical effects of the present application are as follows: the present application can accurately control the process of scraping and coating the conductive material through the design of the mold and the groove, and can effectively control the thickness of the conductive material to avoid the performance degradation caused by uneven thickness. The method can form a fine electrode pattern of several microns on the substrate, ensuring the high precision and high consistency of the electrode grid lines; and the method generates almost no waste, greatly reducing the amount and cost of the conductive material, and the saved conductive material can reduce the production cost and improve the economic benefits; The method has a simple process and high process precision, can achieve rapid production, improve production efficiency, meet the needs of industrial production, and is in line with the concept of green and sustainable development, helping to promote the application of environmentally friendly production processes; and the electrode grid lines prepared by the above method bring high precision, high conductivity, good surface finish, optimized thermal management, and enhanced mechanical strength and durability to photovoltaic cells, which comprehensively improves the performance, efficiency and long-term stability of photovoltaic cells. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 It is a schematic diagram of the process flow of the electrode grid line preparation method of the embodiment of the present application.
[0036] Explanation of the reference numerals: 1. substrate; 2. polymer layer; 3. mold; 4. groove; 5. conductive material; 6. electrode grid line. DETAILED DESCRIPTION
[0037] The following is combined with Figure 1 This application is described in further detail.
[0038] Reference Figure 1 The present application discloses a method for preparing an electrode grid line, which comprises the following steps: S1, providing a substrate 1, and forming a polymer layer 2 on the substrate 1 by coating a polymer solution; before coating, it is necessary to ensure that the surface of the substrate 1 is clean, flat and free of pollution to ensure the quality of the subsequent coating process, and perform surface treatment on the substrate 1 to enhance the adhesion of the polymer layer 2; In this embodiment, a polymer solution is coated on the substrate 1 by a flat coating method, and a polymer layer 2 is obtained after drying. The flat coating method includes spin coating, scraper coating or spray coating, and the specific selection depends on the properties of the polymer used and the required thickness. The coating rate and uniformity need to be controlled during the coating process to ensure the uniform thickness of the polymer layer 2. Specifically, before coating, the substrate 1 is subjected to necessary pretreatment, and the pretreatment method includes cleaning, drying and surface activation to remove pollutants on the surface of the substrate 1, increase the surface roughness, and improve the adhesion of the polymer layer 2; A uniform polymer solution is coated on the substrate 1, and the uniformity and thickness of the coating are controlled. After the coating is completed, the polymer layer 2 is dried or cured under an environmental condition of 90° C. to 110° C. to ensure that its physical and chemical properties meet the requirements. In this embodiment, according to the properties and application requirements of the polymer, further curing treatment may be performed, including but not limited to heating in an oven, so that the polymer layer 2 is further cross-linked and hardened; The material of the substrate 1 includes but is not limited to one of monocrystalline silicon, polycrystalline silicon, gallium arsenide, cadmium telluride, and amorphous silicon film. In this embodiment, preferably, the material of the substrate 1 is polycrystalline silicon; the silicon wafer has good electronic conductivity and stability, and has good thermal stability and thermal conductivity, and is suitable for the manufacture of various electronic devices.
[0039] In this embodiment, the material of the polymer layer 2 is a water-soluble polymer material, and the water-soluble polymer material is one of polyvinyl alcohol (PVA), polypyrrolidone (PVP), polyethylene glycol (PEG), modified polyvinyl alcohol (PVA), sodium polyacrylate (PAA-Na), polyvinyl alcohol-polyacrylic acid (PVA-PAA), and polyvinyl alcohol-polyacrylonitrile (PVA-PAN). In this embodiment, preferably, the material of the polymer layer 2 is polyvinyl alcohol; polyvinyl alcohol is insoluble in organic solvents such as acetone, methanol, and gasoline. Polyvinyl alcohol can be processed by a simple dissolution and coating process, which simplifies the production process. Moreover, since water is used as a solvent, these materials are more environmentally friendly and reduce the use of organic solvents and waste disposal problems.
[0040] S2. Provide a mold 3 corresponding to the required electrode pattern. In this embodiment, a mold 3 matching the required electrode pattern is prepared. The substrate of the mold 3 includes but is not limited to a single crystal silicon substrate, a polycrystalline silicon substrate, a glass substrate, a quartz substrate, a polymer substrate, a copper substrate, a nickel substrate, a copper-nickel alloy substrate, a nickel-iron alloy substrate, an iron-aluminum alloy substrate, and an aluminum alloy substrate; and its surface needs to be accurately engraved or processed into the required electrode pattern, which is expressed as the shape and layout of the electrode, including the required grooves 4, protrusions, and other structural details; Specifically, the mold 3 is aligned with the substrate 1 coated with the polymer layer 2, ensuring that the pattern of the mold 3 is accurately aligned with the position on the polymer layer 2, and the groove 4 corresponding to the electrode pattern is pressed out on the polymer layer 2 through the mold 3; the mold 3 is pressed onto the polymer layer 2 through a hot pressing process, and the hot pressing temperature includes but is not limited to being set between 100-180°C. Preferably, the best hot pressing molding conditions are: hot pressing temperature of 130°C, hot pressing pressure of 10MPa, and hot pressing time of 2min. Under this condition, the groove 4 can be well hot pressed out. Within this temperature and pressure range, the polymer layer 2 will become soft enough, so that the pattern of the mold 3 can be accurately printed on the polymer layer 2, so as to ensure that the polymer layer 2 can evenly form the desired groove 4 structure during the hot pressing process, while avoiding excessive heating to cause degradation or flow of the polymer layer 2; Within this temperature and pressure range, the polymer layer 2 can be uniformly pressed into the mold 3, thereby forming a clear and accurate groove 4 structure, improving the quality and consistency of the product. The relatively low hot pressing temperature can reduce the thermal damage to the polymer layer 2, avoid polymer degradation or failure due to excessive temperature, maintain the performance and stability of the material, and thus improve production efficiency and product consistency. After the hot pressing is completed, the thickness D of the embossed residual layer is 0.5-2 μm, that is, a certain distance D should be kept between the bottom of the groove 4 and the substrate 1, and the distance D is 0.5-2 μm. This distance can effectively avoid direct contact between the film 3 and the substrate 1, thereby reducing the risk of substrate 1 cracking due to mechanical stress, helping to maintain the integrity of the substrate 1 during operation, and improving the stability and reliability of the entire system; After completing these steps, the mold 3 is removed, and the polymer layer 2 can be subsequently processed according to actual needs, such as hardening or cleaning, to ensure the clarity and stability of the groove 4, and finally form an electrode pattern that meets the design requirements.
[0041] The longitudinal cross-sectional shape of the groove 4 includes but is not limited to a rectangle or a trapezoid. In the present embodiment, the longitudinal cross-sectional shape of the groove 4 is a rectangle with a height-to-width ratio of 2:1. The groove 4 is designed to have a rectangular cross-sectional geometry, which simplifies the process and ensures uniform filling of the conductive material 5. In addition, the edges of the rectangular groove 4 are sharp, which can better ensure the contact and conductivity of the electrode, while reducing gaps or insufficient materials that occur during the filling process.
[0042] S2-1: After the hot pressing process is completed, further processing is performed on the polymer layer 2 to remove part of the polymer layer 2 so that the bottom wall of the groove 4 is on the same level as the top surface of the substrate 1. In this process, including but not limited to weakening the height of the polymer layer 2 by reactive ion etching technology (RIE etching), the removed part of the polymer layer 2 is a structure of 0.5-2 μm between the bottom of the groove 4 and the substrate 1; Specifically, select appropriate RIE etching equipment, set etching parameters according to the polymer material used, ensure that the etching system is clean, and prepare the required gas, such as oxygen or fluorinated gas. Preferably, oxygen is selected as the gas; according to the thickness of the polymer layer 2 and the required etching depth, set the etching power, gas flow, etching time and gas pressure to ensure the uniformity and accuracy of the etching; place the substrate 1 in the RIE etching chamber and start the etching process. During the etching process, reactive ions will produce chemical reactions and physical etching on the polymer surface, thereby removing part of the polymer layer 2 until the bottom of the groove 4 is flush with the top surface of the substrate 1; after the etching is completed, clean the substrate 1 to remove residual etching byproducts and impurities. In this embodiment, deionized water or other appropriate cleaning solvents can be used to ensure the surface is clean, and check the uniformity and alignment of the groove 4.
[0043] RIE etching technology can be used to accurately remove part of the polymer layer 2, weaken the height of the polymer layer 2, ensure that the remaining polymer layer 2 in the groove 4 on the substrate 1 is etched away, and the surface of the substrate 1 is exposed. RIE etching can remove the polymer layer 2 in a relatively short time, and at the same time can provide a uniform etching effect and maintain the surface quality of the groove bottom; and after etching, the conductive material 5 subsequently applied in the groove 4 can directly contact the substrate 1, which enhances the conductive performance and contact quality of the conductive material 5, and ensures that the conductive material 5 can form a more stable electrode structure, thereby improving production efficiency and yield rate.
[0044] S3, applying the conductive material 5 on the polymer layer 2. In this embodiment, the conductive material 5 is applied on the polymer layer 2 by a flat coating technique but is not limited thereto, so that the conductive material 5 fills the groove 4, and the excess conductive material 5 is scraped off; Specifically, select a suitable flat coating tool, such as a coating knife or a scraper, and evenly apply the conductive material 5 on the surface of the polymer layer 2 to ensure that the material can penetrate into and fill all the grooves 4. During the coating process, pay special attention to the filling of the groove 4 area to ensure that the conductive material 5 completely covers the bottom and side walls of the groove 4; use a flat tool (such as a scraper) to scrape off excess conductive material 5 on the surface to keep the conductive material 5 in the groove 4 flush with the surface of the polymer layer 2. The scraper should be kept parallel to the surface to obtain a uniform coating thickness and avoid damaging the polymer layer 2; after coating, check the filling effect to ensure that the conductive material 5 inside the groove 4 is uniform and without omission, and perform trimming if necessary to remove unnecessary materials or repair uneven areas.
[0045] The conductive material 5 is one of silver paste, copper paste, aluminum paste and a mixture thereof. In this embodiment, preferably, the conductive material 5 is silver paste. Silver paste can provide excellent conductivity, help reduce the resistance of electronic devices, improve performance and efficiency, and can provide efficient and stable conductive performance. At the same time, it can adapt to different substrates and manufacturing processes to meet the needs of high-performance electronic products. In this embodiment, the material polyvinyl alcohol of the polymer layer 2 will not react with the organic solvent in the silver paste of the conductive material 5, so that the polymer layer 2 and the conductive material 5 will not be bonded together. As a result, the silver paste of the conductive material 5 can maintain its own shape, reducing the difference in the shapes of the printed conductive materials 5 and affecting their conductive properties.
[0046] S4, drying the conductive material 5, the conductive material 5 is dried in an oven, and the drying temperature of the conductive material 5 is 100-200° C. Using this temperature range can ensure that the conductive material 5 is fully dried to form a stable conductive layer, and help to enhance the adhesion between the conductive material 5 and the substrate 1, reduce the risk of peeling or falling off, and improve its electrical properties and conductivity; Specifically, according to the type of conductive material 5 and the manufacturer's recommendations, the temperature of the oven is set between 100°C and 200°C. This temperature range is generally suitable for drying most conductive materials 5, ensuring that the material is fully dried without overheating or damage; carefully place the sample coated with the conductive material 5 into the oven, set the oven timer, and ensure that the sample is dried for a sufficient time at the set temperature. The drying time is determined according to the specific requirements and layer thickness of the conductive material 5, usually 0.5min-10min. Follow the drying time recommendations provided by the material manufacturer to ensure the best drying effect; During the drying process, the temperature in the oven and the state of the sample are continuously monitored to ensure that the temperature inside the oven remains stable, and to avoid adverse effects of excessively high or low temperatures on the drying effect of the conductive material 5. If temperature fluctuations or other abnormal conditions occur, timely adjustments or corrections are made. After the drying time is over, the sample is taken out of the oven and the drying effect of the conductive material 5 is checked to ensure that the material is evenly dried without bubbles, shedding or other defects. The drying quality can be evaluated by visual inspection or by using appropriate test methods.
[0047] S5, after drying, dissolving the polymer layer 2, including but not limited to using hot water at 60-80°C to dissolve the polymer layer 2. In this embodiment, hot water at 70°C is used to dissolve the polymer layer 2. Hot water at a higher temperature accelerates the dissolution process of the polymer, shortens the processing time, and improves production efficiency. Hot water helps to overcome the crystalline structure of the polymer, making it dissolve more evenly and forming a more stable solution. Specifically, after drying, carefully place the dried sample in 70°C hot water to ensure that the polymer layer 2 is completely immersed. After soaking in 70°C hot water for a certain period of time, the polymer layer 2 will gradually dissolve. Check the sample regularly to observe the dissolution of the polymer layer 2. When the polymer layer 2 is completely dissolved, remove the sample from the hot water and rinse it with clean water to remove any remaining polymer solution. Place the sample in a dry environment to ensure complete drying to avoid residual moisture affecting subsequent processing. Check the sample after removing the polymer layer 2 to confirm the integrity and surface quality of the conductive material 5, ensure that there is no damage or material missing, and ensure that subsequent applications and integration can proceed smoothly.
[0048] S6, further sintering the conductive material 5 to form a continuous, complete and non-deformed electrode grid line 6, the sintering temperature of the conductive material 5 is 600-800° C.; Specifically, including but not limited to selecting an appropriate sintering furnace, setting the temperature of the sintering furnace between 600°C and 800°C, this temperature range is suitable for the sintering of the conductive material 5, ensuring that it achieves the required electrical conductivity and structural strength; carefully placing the processed sample into the sintering furnace, starting the sintering furnace, and gradually heating it to the set temperature. During the heating process, the temperature is kept stable to ensure that the conductive material 5 is evenly sintered. The heating time is usually determined according to the thickness of the material and specific requirements; after the sintering process is completed, the temperature in the furnace is gradually lowered to room temperature to avoid rapid cooling to prevent the material from cracking or deforming due to thermal stress. After cooling is completed, the formed electrode grid line 6 is checked to ensure that its structure is intact and the electrical conductivity meets the requirements, and to check whether there is any uneven sintering or material defects; High-temperature sintering is used to form a firm connection between the particles of the conductive layer, improve the bonding force between the layers, reduce the peeling problem, thereby enhancing the mechanical strength and stability of the overall structure. At high temperatures, the particles in the conductive material 5 can be effectively fused, significantly improving the conductivity and optimizing the conductive performance.
[0049] The present application also provides a photovoltaic cell, comprising an electrode grid line 6 prepared by the preparation method described above; The longitudinal cross-sectional shape of the electrode grid line 6 includes but is not limited to a rectangle or a trapezoid; wherein the height of the rectangle is 10±2μm, and the aspect ratio of the rectangle is 2:1; the base angle of the trapezoid is 30°-70°, the height of the trapezoid is 10±2μm, and the aspect ratio of the trapezoid is 2:1; the optimal shape of the electrode grid line 6 should be comprehensively considered according to the type, size, material and other aspects of the photovoltaic cell, so as to provide a larger contact area, reduce resistance, and distribute current more evenly, which can reduce hot spots and improve overall efficiency, and can better control the propagation direction of light, reduce reflection loss, increase light absorption, and help to increase the path length of light inside the battery, thereby increasing light absorption efficiency; The electrode grid lines 6 prepared by the above method bring high precision, high conductivity, good surface finish, optimized thermal management, and enhanced mechanical strength and durability to the photovoltaic cell, which comprehensively improves the performance, efficiency and long-term stability of the photovoltaic cell; the mold 3 is used to press out precise grooves 4 on the polymer layer 2, ensuring the high precision of the electrode grid lines 6 pattern. This precise patterning helps to optimize the photoelectric conversion efficiency and current collection capacity of the photovoltaic cell; the conductive material 5 is filled and dried and sintered twice, so that the electrode grid lines 6 have excellent conductivity. The highly conductive electrode grid lines 6 can effectively collect the current generated by the battery, reduce resistance and energy loss, and thus improve the overall power output of the battery; the preparation method supports different electrode pattern designs, so that the structure of the electrode grid lines 6 can be optimized according to the specific needs of the photovoltaic cell, and the flexible design can improve the photoelectric conversion efficiency and adapt to different application scenarios.
[0050] The implementation principle of the embodiment of the present application is: by accurately controlling the process of scraping and coating the conductive material 5 through the design of the mold 3 and the groove 4, the thickness of the conductive material 5 can be effectively controlled to avoid performance degradation caused by uneven thickness. This method can form a fine electrode pattern of several microns on the substrate 1, ensuring the high precision and high consistency of the electrode grid line 6; and this method generates almost no waste, greatly reducing the amount and cost of the conductive material 5, and the saved conductive material 5 can reduce production costs and improve economic benefits; this method has a simple process and high process precision, can achieve rapid production, improve production efficiency, meet the needs of industrialized production, and can conform to the concept of green and sustainable development, and help promote the application of environmentally friendly production processes.
[0051] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.
Claims
1. A method for preparing an electrode grid line, characterized in that: The following steps are involved: S1, providing a substrate, and forming a polymer layer on the substrate; S2, providing a mold corresponding to the required electrode pattern, and pressing a groove corresponding to the electrode pattern on the polymer layer through the mold; S3, applying a conductive material on the polymer layer, so that the conductive material fills the groove, and scraping off the excess conductive material; S4, drying the conductive material; S5, after drying, dissolving the polymer layer; S6, sintering the conductive material to form the electrode grid lines.
2. The method for preparing an electrode grid line according to claim 1, characterized in that: In the step S2, the thickness of the imprinted residual layer is 0.5-2 μm.
3. The method for preparing an electrode grid line according to claim 2, characterized in that: The method further includes step S2-1 between S2 and S3: removing a portion of the polymer layer so that the bottom wall of the groove and the top surface of the substrate are on the same horizontal plane.
4. The method for preparing an electrode grid line according to claim 3, characterized in that: In S2-1, the polymer layer is etched by reactive ion etching technology to remove a portion of the polymer layer.
5. The method for preparing an electrode grid line according to claim 1, characterized in that: In S2, the groove is hot-pressed on the polymer layer by the mold, and the hot-pressing temperature is 100-180°C.
6. The method for preparing an electrode grid line according to claim 1, characterized in that: In S4, the drying temperature of the conductive material is 100-200°C.
7. The method for preparing an electrode grid line according to claim 1, characterized in that: The material of the polymer layer is a water-soluble high molecular material.
8. The method for preparing an electrode grid line according to claim 7, characterized in that: The water-soluble polymer material is one of polyvinyl alcohol, polyvinyl pyrrolidone, polyethylene glycol, modified polyvinyl alcohol, sodium polyacrylate, polyvinyl alcohol-polyacrylic acid, and polyvinyl alcohol-polyacrylonitrile.
9. The method for preparing an electrode grid line according to claim 1, characterized in that: In S5, hot water at 60-80° C. is used to dissolve the polymer layer.
10. The method for preparing an electrode grid line according to claim 1, characterized in that: In S6, the sintering temperature of the conductive material is 600-800°C.
11. The method for preparing an electrode grid line according to claim 1, characterized in that: The material of the substrate is one of single crystal silicon, polycrystalline silicon, gallium arsenide, cadmium telluride, and amorphous silicon film.
12. The method for preparing an electrode grid line according to claim 1, characterized in that: The conductive material is one of silver paste, copper paste, aluminum paste and a mixture thereof.
13. The method for preparing an electrode grid line according to claim 1, characterized in that: The longitudinal section of the groove is in a shape of a rectangle or a trapezoid.
14. The method for preparing an electrode grid line according to claim 1, characterized in that: The substrate of the mold is one of a single crystal silicon substrate, a polycrystalline silicon substrate, a glass substrate, a quartz substrate, a polymer substrate, a copper substrate, a nickel substrate, a copper-nickel alloy substrate, a nickel-iron alloy substrate, an iron-aluminum alloy substrate, and an aluminum alloy substrate.
15. A photovoltaic cell, characterized in that: The electrode grid line comprises the electrode grid line prepared by the preparation method according to any one of claims 1 to 14.
16. The photovoltaic cell according to claim 15, characterized in that: The longitudinal cross-section of the electrode grid line is rectangular or trapezoidal, the height of the rectangle is 10±2 μm, the aspect ratio of the rectangle is 2:1, the bottom angle of the trapezoid is 30°-70°, the height of the trapezoid is 10±2 μm, and the aspect ratio of the trapezoid is 2:1.
